A qualitative study of the factors that influence mothers when choosing drinks for their young children - Hoare, Alexandria (BioMed Central, 2014)
BACKGROUND: The consumption of sweetened beverages is a known common risk factor for the development of obesity and dental caries in children and children consume sweet drinks frequently and in large volumes from an early age. The aim of this study was to examine factors that influence mothers when choosing drinks for their children. METHOD: Semi-structured interviews (n = 32) were conducted with a purposive sample of mothers of young children from Victoria’s Barwon South Western Region (selected from a larger cohort study to include families consuming different types of water, and different socioeconomic status and size). Inductive thematic analysis was conducted on transcribed interviews. RESULTS: Several themes emerged as influencing child drink choice. Child age: Water was the main beverage for the youngest child however it was seen as more acceptable to give older children sweetened beverages. Child preference and temperament: influencing when and if sweet drinks were given; Family influences such as grandparents increased children’s consumption of sweet drinks, often providing children drinks such as fruit juice and soft drinks regardless of maternal disapproval. The Setting: children were more likely to be offered sweetened drinks either as a reward or treat for good behaviour or when out shopping, out for dinner or at parties. CONCLUSIONS: Limiting intake of sweet drinks is considered an important step for child general and oral health. However, the choice of drinks for children has influences from social, environmental and behavioural domains, indicating that a multi-strategy approach is required to bring about this change.